Preparation method and application of electronic phase change material doped with nickel sulfide alloy compound

Through the design of doping element components and synthesis process, the prepared doped nickel sulfide alloy compound achieves resistivity mutation near room temperature, solving the problem that NiS alloy compound cannot achieve resistivity mutation near room temperature, and has a high degree of resistivity mutation and Good mechanical properties, suitable for a variety of functional devices.

CN116282235BActive Publication Date: 2024-12-20UNIV OF SCI & TECH BEIJING
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202211590430.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-12-12
Publication Date
2024-12-20
Estimated Expiration
2042-12-12

AI Technical Summary

Technical Problem

The existing NiS alloying compounds cannot achieve resistivity mutations near room temperature, limiting their applications in mutational thermistor devices, strong correlation logic devices, and infrared camouflage coatings.

Method used

Through the design of doping element components and synthesis process, doping nickel sulfide alloy compounds are prepared, and solid phase reaction, quenching and heat treatment are used to achieve continuous regulation of the resistivity sudden temperature near room temperature and above, and through the types of doping elements and proportional adjustment to the degree of resistivity mutation.

Benefits of technology

The resistivity mutation degree of doped sulfur nickel compound has been achieved by exceeding one order of magnitude, with good mechanical properties and processability, and is suitable for applications such as mutation thermistor devices, strong correlation logic devices and infrared camouflage coatings.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116282235B_ABST
    Figure CN116282235B_ABST
Patent Text Reader

Abstract

The present invention belongs to the field of alloy compound electronic phase change materials, and relates to a preparation method and application of a doped nickel sulfide alloy compound electronic phase change material. By doping element components and synthetic process design, the resistivity mutation temperature of the element-doped nickel sulfide alloy compound is continuously regulated in the range near room temperature and above, and the resistivity mutation degree exceeds one order of magnitude. Compared with traditional oxide electronic phase change materials, the advantages of the alloy compound electronic phase change material prepared by the present invention are that it has good mechanical properties and processability, and a high resistivity mutation degree. The prepared doped nickel sulfur compound can be further made into a mutation thermistor device, a strongly correlated logic device, an infrared camouflage coating, and a thermochromic coating, thereby realizing the application of a mutation functional device near room temperature.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the field of alloy compound electronic phase change materials, and specifically relates to a method of achieving the prepared doped nickel sulfide alloy compound through doping element components and synthesis process design, which has the characteristics of continuous regulation of resistivity mutation temperature in the range near room temperature and above and resistivity mutation degree exceeding one order of magnitude, and has considerable application value in mutation thermistor devices, strongly correlated logic devices, infrared camouflage coatings, and thermochromic coatings. Background Art

[0002] Strongly correlated semiconductor electronic phase change materials triggered by external fields can be applied to thermistor devices, infrared sensors, and thermochromic coating materials. Existing traditional electronic phase change materials are mostly concentrated on vanadium dioxide and rare earth nickel-based oxide materials, which have the advantages of temperature-induced phase change, hydrogen-induced phase change, and adjustable phase change temperature. However, metastable oxides are easy to deteriorate in an air atmosphere, and their mechanical properties are relatively poor and their brittleness is high, which greatly limits the application potential of semiconductor electronic phase change materials. In comparison, alloy compounds have good stability, ductility, high hardness and good mechanical properties. Therefore, NiS alloy compounds with resistivity mutation function need to be further explored. For the Ni-S system, nickel sulfide has three variants: α, β, and γ. Among them, only the β-phase NiS has a sharp metal-insulator phase transition (MIT) characteristic, which is similar to the classic vanadium dioxide (VO 2 ) has similar temperature-induced phase change characteristics. Compared with VO 2 Other types of temperature-induced phase change materials, such as NiS, can be substituted by the S-site element in NiS and doped with Se to control the distance between Ni atoms and the overlap between Ni 3d (conduction band) and S 2p (valence band), thereby achieving the adjustment of the phase transition temperature within a wide range of nearly 100K. In addition to changing the type of rare earth elements, the temperature-induced phase change performance of NiS can also be further adjusted by pressure and cation substitution (vanadium, copper, manganese). Since the phase transition of NiS is not accompanied by a change in the symmetry of the crystal structure, it is a typical Mott phase change material driven by electron-electron interaction. This unique advantage makes it a typical strong electron correlation material system with considerable research value.

[0003] Although NiS is a classic electronic phase change material due to its temperature-induced phase change characteristics, its phase change temperature is lower than room temperature, and according to previous reports, the regulation of the temperature-induced phase change characteristics can only reduce the resistivity mutation temperature, and there is no report on increasing its resistivity mutation temperature, which limits the application of NiS materials as mutation thermistors near room temperature. In summary, the art lacks a process method that can cause NiS alloy compounds to undergo a resistivity mutation near room temperature, so that NiS can be applied to mutation thermistor devices near room temperature, strongly correlated logic devices, infrared camouflage coatings, and thermochromic coatings. Summary of the invention

[0004] The purpose of the present invention is to achieve continuous regulation of the resistivity mutation temperature of element-doped nickel sulfide alloy compounds in the range near room temperature and above, and the resistivity mutation degree exceeds one order of magnitude by designing doped element components and synthesis processes. Compared with traditional oxide electronic phase change materials, the advantages of the alloy compound electronic phase change material prepared by the present invention are that it has good mechanical properties and processability, and a high resistivity mutation degree. The prepared doped nickel sulfur compound can be further made into a mutation thermistor device, a strongly correlated logic device, an infrared camouflage coating, and a thermochromic coating, thereby realizing the application of mutation functional devices near room temperature.

[0005] The present invention provides a method for preparing an electronic phase change material doped with a nickel sulfide alloy compound, which is characterized in that the resistivity mutation temperature of the prepared nickel sulfide alloy compound is continuously adjusted in a range near room temperature and above, and the resistivity mutation degree exceeds one order of magnitude, through a solid phase reaction between pre-synthesized NiS and a doping element sulfide, quenching, and a subsequent heat treatment process combined with the design of the doping element composition and content, so as to realize the application of the electronic device and optical device thereof, and the main steps include:

[0006] (1) synthesizing a nickel sulfide parent phase by solid phase reaction with nickel and sulfur, wherein the nickel sulfide material is an α phase, has a hexagonal crystal structure, and a space group of R3mH, and does not have an electronic phase transition characteristic triggered by a characteristic temperature; synthesizing a chalcogenide compound of the doping element by solid phase reaction with a doping element and sulfur, selenium, and tellurium chalcogenide elements, wherein the doping element is in a +2 valence, has a hexagonal structure, and has a lattice parameter similar to that of β-phase nickel sulfide having an electronic phase transition characteristic, and the chalcogenide compound of the doping element has a semiconductor phase transport characteristic or a metal-insulator phase transition characteristic with a characteristic temperature higher than room temperature;

[0007] (2) Grinding the synthesized nickel sulfide parent phase and the doping element sulfide compound into powder, uniformly mixing them according to a certain doping ratio and cold pressing them into shape; in a vacuum or protective atmosphere, heating the mixed powder after cold pressing to above the transition temperature from the α phase to the β phase of nickel sulfide by direct heating with a resistance wire, or light heating, or plasma sintering triggered by a pulse current flowing through the sample, and rapidly cooling to below room temperature after keeping the temperature for a period of time, thereby retaining the high-temperature β phase; thereafter, direct heating annealing or light annealing is performed for a period of time in the temperature range of 0-100°C above the resistivity mutation temperature to eliminate the crystal defects caused by the extremely cold quenching process, so that the prepared high-temperature hexagonal structure doped nickel sulfide compound has a resistivity mutation characteristic of more than one order of magnitude in the range of the metal-insulator phase transition temperature above 0°C;

[0008] (3) The doped nickel sulfide alloy compound with a high-temperature hexagonal structure prepared in step (2) has the property of sudden changes in resistivity, infrared reflectivity, infrared transmittance, and infrared emissivity under characteristic temperature triggering, and the above characteristic temperature can be continuously adjusted in the range of 0°C to 300°C by adjusting the doping ratio of the sulfide compound of the doping element and nickel sulfide.

[0009] Furthermore, the chalcogenide compound of the doping element in step (1) is selected from FeS, CrS, FeSe, FeTe, FeS x Se 1-x ; By adjusting the type and doping ratio of the doping element chalcogenide compound, the resistivity mutation temperature and resistivity mutation degree of the doped nickel sulfide alloy compound can be controlled. In a preferred example, FeS and CrS are preferred as doping chalcogenides, FeS has a hexagonal structure, space group P63 / mmc, and has a resistivity mutation of more than one order of magnitude near 300°C; CrS has a hexagonal structure, space group P63 / mc, and has a resistivity mutation of more than one order of magnitude near 430°C; the lattice selective doping material is 10% ferrous sulfide co-doped in the parent phase nickel sulfide, so that the nickel sulfide doping material has a resistivity mutation of more than one order of magnitude near room temperature and above.

[0010] Furthermore, by controlling the heat treatment process after the nickel sulfide parent phase and the doping element sulfide compound are mixed in step (2), the resistivity mutation characteristics of the doped nickel sulfide alloy compound near and above room temperature are achieved; the key technology is: in a vacuum or argon or helium protective atmosphere, a resistance wire is used to directly heat a thicker block sample to fully react with the solid phase, or a thin slice sample is light-heated to maintain the surface morphology of the film, or a plasma sintering method is triggered by a pulse current flowing through the sample; the mixed powder after cold pressing is heated to the transition point from the α phase to the β phase of the nickel sulfide. The β-phase nickel sulfide is obtained by heating the nickel sulfide to above the transition temperature; after keeping the temperature for more than 12 hours, the β-phase nickel sulfide is quenched in liquid nitrogen or ice water mixture to below room temperature, thereby retaining the high-temperature β-phase; thereafter, in the temperature range of 0-100°C above the resistivity mutation temperature, a long-term direct heating annealing of 1 to 24 hours or a short-term rapid light annealing of 30 seconds to 5 minutes is performed to eliminate the crystal defects caused by the extremely cold quenching process, so that the prepared doped nickel sulfide compound has a resistivity mutation characteristic of more than one order of magnitude in the range of the metal insulator phase transition temperature above 0°C. In a preferred embodiment, a certain amount of cold-pressed mixed powder is heated to 700°C and kept for 24 hours in an argon protective atmosphere, then quenched to below room temperature, and annealed at 100°C for 24 hours to obtain a doped nickel sulfide alloy compound with fewer defects and uniform doping.

[0011] The application of the electronic phase change material doped with nickel sulfide alloy compound prepared by the above method, the electronic phase change material can be further processed into a regular shape and made into a sudden change thermistor, a strong switch logic device, and a pressure sensor through electrode leads; it can also be used for thermochromic coatings and infrared camouflage coatings. In a preferred example, a nickel sulfide alloy compound material doped with 10% FeS is selected to be packaged into a sudden change thermistor device, and the nickel sulfide doped device has a 20-fold resistivity sudden change electrical characteristic at 0°C.

[0012] Furthermore, the prepared electronic phase change material is cut into small chips of regular shape, and silver or platinum electrode materials are sprayed or brushed on two opposite surfaces of the chip to obtain ohmic contact, and connected to copper-nickel alloy leads by welding. Finally, they are packaged with high thermal conductivity epoxy resin sealant to prepare sudden change thermistor devices and strongly correlated logic devices. The devices have excellent electrical properties with resistivity sudden changes of more than one order of magnitude near room temperature and above.

[0013] Furthermore, the application of the electronic phase change material doped with nickel sulfide alloy compound prepared by the method as described above is characterized in that the prepared electronic phase change material can be further crushed into powder, an organic copper complex filler is added, and a coating is made by electrochemical deposition or vacuum deposition and applied to thermochromic and infrared camouflage coatings.

[0014] After extensive and in-depth research, the present invention realizes the continuous regulation of the resistivity mutation temperature of the element-doped nickel sulfide alloy compound near room temperature and above through the design of doping element components and synthesis process, and the resistivity mutation degree exceeds one order of magnitude. Compared with the previously reported phase change regulation method, the biggest feature of this method is: it has good mechanical properties and processability, and a high resistivity mutation degree; the prepared doped nickel sulfur compound can be further made into a mutation thermistor device, a strongly correlated logic device, an infrared camouflage coating, and a thermochromic coating, thereby realizing the application of a mutation functional device near room temperature. BRIEF DESCRIPTION OF THE DRAWINGS

[0015] Figure 1 The resistance-temperature relationship curve of the NiS alloy compound doped with 20% FeS prepared by the method of the present invention.

[0016] Figure 2 The electron scanning electron microscope image is of a NiS alloy compound doped with 20% FeS prepared by the method of the present invention.

[0017] Figure 3 The invention discloses an X-ray diffraction spectrum of a NiS alloy compound doped with 20% FeS prepared by the method of the invention.

[0018] Table 1 is a summary of the process preparation conditions of the examples. DETAILED DESCRIPTION

[0019] Unless otherwise specified, the various raw materials of the present invention can be obtained from the market; or prepared according to conventional methods in the art. Unless otherwise defined or specified, all professional and scientific terms used herein have the same meanings as those familiar to those skilled in the art. In addition, any methods and materials similar or equivalent to those described herein can be applied to the methods of the present invention.

[0020] Other aspects of the present invention will be apparent to those skilled in the art in view of the disclosure herein.

[0021] The present invention will be further described below in conjunction with specific examples. It should be understood that these examples are only used to illustrate the present invention and are not intended to limit the scope of the present invention. The experimental methods in the following examples without specifying specific conditions are usually carried out under conventional conditions or under conditions recommended by the manufacturer.

[0022] Test method: We use XRD, SEM, XPS, and Verslab to characterize the synthesized nanopowders. The characterization methods are performed according to the general standards in the field.

[0023] Embodiment 1:

[0024] NiS and FeS were weighed in a stoichiometric ratio of 4:1, then ground in an agate mortar for 15 minutes, and then the evenly ground powder was cold pressed into sheets. -2 The samples were sintered at 700°C for 24 hours using a resistance wire in a Pascal vacuum atmosphere, quenched in an ice-water mixture to below room temperature, and annealed at 100°C for 24 hours. Figure 1 The temperature resistance relationship diagram of the FeS-doped alloy compound prepared according to Example 1 is shown in FIG. Figure 2 is a scanning electron microscope image. Figure 3 It is an X-ray diffraction spectrum. As can be seen from the figure, the prepared doped nickel sulfide alloy compound has no impurities, good surface uniformity, and has an electrical characteristic of a resistivity mutation degree of more than 15 times at a characteristic temperature of 25 degrees Celsius, proving that the method described in this article can prepare doped nickel sulfide alloy compounds. If the annealing heat process is lacking, the prepared doped nickel sulfide alloy compound has more grain defects and poor electrical properties, and no resistivity mutation can be observed near room temperature, proving that the doped nickel sulfide alloy compound prepared without the annealing process method described in this article does not have the resistivity mutation characteristic near room temperature.

[0025] Embodiment 2:

[0026] NiS and FeSe were weighed in a stoichiometric ratio of 9:1, then ground in an agate mortar for 15 minutes, and the evenly ground powder was cold pressed into sheets, directly heated to 600 degrees Celsius by a resistance wire in a 20 Pa helium atmosphere, sintered for 48 hours, quenched in liquid nitrogen to below room temperature, and light annealed at 100 degrees Celsius for 1 minute. The prepared doped nickel sulfide alloy compound has a pure phase structure, good surface uniformity, and an electrical property with a resistivity mutation degree of more than 21 times at 0 degrees Celsius, proving that the method described in this article can prepare doped nickel sulfide alloy compounds.

[0027] Embodiment 3:

[0028] NiS and FeTe were weighed in a stoichiometric ratio of 9:1, then ground in an agate mortar for 15 minutes, and the evenly ground powder was cold pressed into sheets, sintered at 500 degrees Celsius for 2 hours by light heating in a 20 Pascal argon atmosphere, quenched in an ice-water mixture to below room temperature, and light annealed at 200 degrees Celsius for 30 seconds. The prepared doped nickel sulfide alloy compound has a pure phase structure, good surface uniformity, and an electrical property with a resistivity mutation degree of more than 14 times at 180 degrees Celsius, proving that the method described in this article can prepare doped nickel sulfide alloy compounds.

[0029] Embodiment 4:

[0030] NiS and CrS were weighed in a stoichiometric ratio of 4:1, then ground in an agate mortar for 15 minutes, and then the evenly ground powder was cold pressed into sheets. -2 The sintering was carried out at 1000 degrees Celsius for 1 hour in a Pascal vacuum atmosphere by using a pulse current-triggered plasma sintering method, quenched in an ice-water mixture to below room temperature, and light annealed at 400 degrees Celsius for 5 minutes. The prepared doped nickel sulfide alloy compound has a pure phase structure, good surface uniformity, and an electrical property with a resistivity mutation degree of more than 13 times at a temperature of 300 degrees Celsius, which proves that the method described in this article can prepare doped nickel sulfide alloy compounds.

[0031] Embodiment 5:

[0032] NiS, FeS, and FeSe were weighed in a stoichiometric ratio of 8:1:1, then ground in an agate mortar for 15 minutes, and then the evenly ground powder was cold pressed into sheets. -2 The alloy was directly heated to 700 degrees Celsius by a resistance wire in a Pascal vacuum atmosphere, sintered for 36 hours, quenched in liquid nitrogen to below room temperature, and annealed at 100 degrees Celsius for 12 hours. The prepared doped nickel sulfide alloy compound has a pure phase structure, good surface uniformity, and an electrical property with a resistivity mutation degree of more than 19 times at 0 degrees Celsius, which proves that the method described in this article can prepare doped nickel sulfide alloy compounds.

[0033] Embodiment 6:

[0034] NiS, FeS, and FeTe were weighed in a stoichiometric ratio of 7:2:1, then ground in an agate mortar for 15 minutes, and the evenly ground powder was cold pressed into sheets, directly heated to 500 degrees Celsius by a resistance wire in a 20 Pa argon atmosphere, sintered for 48 hours, quenched in an ice-water mixture to below room temperature, and annealed at 150 degrees Celsius for 6 hours. The prepared doped nickel sulfide alloy compound has a pure phase structure, good surface uniformity, and an electrical property with a resistivity mutation degree of more than 13 times at 80 degrees Celsius, proving that the method described in this article can prepare doped nickel sulfide alloy compounds.

[0035] Embodiment 7:

[0036] NiS, FeSe, and FeTe were weighed in a stoichiometric ratio of 8:1:1, then ground in an agate mortar for 15 minutes, and then the ground powder was cold pressed into sheets for 10 -2The sintering was carried out at 700 degrees Celsius for 1 hour in a Pascal vacuum atmosphere by using a pulse current-triggered plasma sintering method, quenched in an ice-water mixture to below room temperature, and light annealed at 200 degrees Celsius for 2 minutes. The prepared doped nickel sulfide alloy compound has a pure phase structure, good surface uniformity, and an electrical property with a resistivity mutation degree of more than 18 times at 120 degrees Celsius, which proves that the method described in this article can prepare doped nickel sulfide alloy compounds.

[0037] Embodiment 8:

[0038] NiS, FeS, and CrS were weighed in a stoichiometric ratio of 7:2:1, and then ground in an agate mortar for 15 minutes. The evenly ground powder was then cold-pressed into sheets. -2 The alloy was directly heated to 900 degrees Celsius by a resistance wire in a Pascal vacuum atmosphere, sintered for 24 hours, quenched in an ice-water mixture to below room temperature, and annealed at 350 degrees Celsius for 6 hours. The prepared doped nickel sulfide alloy compound has a pure phase structure, good surface uniformity, and an electrical property with a resistivity mutation degree of more than 10 times at 300 degrees Celsius, which proves that the method described in this article can prepare doped nickel sulfide alloy compounds.

[0039] Embodiment 9:

[0040] NiS, FeSe, and CrS were weighed in a stoichiometric ratio of 8:1:1, then ground in an agate mortar for 15 minutes, and the evenly ground powder was cold pressed into sheets, directly heated to 850 degrees Celsius by a resistance wire in a 20 Pa helium atmosphere, sintered for 48 hours, quenched in an ice-water mixture to below room temperature, and annealed at 300 degrees Celsius for 1 hour. The prepared doped nickel sulfide alloy compound has a pure phase structure, good surface uniformity, and an electrical property with a resistivity mutation degree of more than 14 times at 220 degrees Celsius, proving that the method described in this article can prepare doped nickel sulfide alloy compounds.

[0041] Embodiment 10:

[0042] NiS, FeTe, and CrS were weighed in a stoichiometric ratio of 8:1:1, then ground in an agate mortar for 15 minutes, and the evenly ground powder was cold pressed into sheets, directly heated to 800 degrees Celsius by a resistance wire in a 20 Pa argon atmosphere, sintered for 48 hours, quenched in an ice-water mixture to below room temperature, and light annealed at 300 degrees Celsius for 1 minute. The prepared doped nickel sulfide alloy compound has a pure phase structure, good surface uniformity, and an electrical property with a resistivity mutation degree of more than 13 times at 260 degrees Celsius, proving that the method described in this article can prepare doped nickel sulfide alloy compounds.

[0043] Embodiment 11:

[0044] NiS, FeS, FeSe, and FeTe were weighed in a stoichiometric ratio of 7:1:1:1, and then ground in an agate mortar for 15 minutes. The evenly ground powder was then cold-pressed into sheets. -2 The prepared nickel sulfide alloy compound has a pure phase structure, good surface uniformity, and an electrical property with a resistivity mutation degree of more than 50 times at 150 degrees Celsius, which proves that the method described in this article can prepare a nickel sulfide alloy compound.

[0045] Embodiment 12:

[0046] The 20% FeS-doped nickel sulfide alloy compound material prepared in Example 1 is cut into small rectangular chips with regular shapes using a high-speed semiconductor cutting saw; silver or platinum electrode materials are sprayed or brushed on two opposite surfaces of the chip to obtain ohmic contact; they are connected to copper-nickel alloy leads by welding, and during the welding process, the thermistor chip is loaded on a lead frame, which relies on the spring tension of the lead to keep the chip fixed during the welding process; finally, a sudden change thermistor device is prepared by encapsulation with a high thermal conductivity epoxy resin sealant, which has excellent electrical characteristics of a resistivity sudden change of more than 15 times at a characteristic temperature of 25 degrees Celsius.

[0047] Embodiment 13:

[0048] The material prepared in Example 2 was further crushed into powder, an organic copper complex filler was added, and an infrared camouflage coating and a thermochromic coating were prepared by electrochemical deposition. The infrared reflectivity, infrared refractive index, and infrared transmittance of the coating had a 20-fold mutation near 0 degrees Celsius.

[0049] The above description is only a preferred embodiment of the present invention and is not intended to limit the scope of the substantial technical content of the present invention. The substantial technical content of the present invention is broadly defined in the scope of the claims of the application. Any technical entity or method completed by others, if it is exactly the same as that defined in the scope of the claims of the application or an equivalent variation, will be deemed to be included in the scope of the claims.

[0050] Table 1

[0051]

Claims

1. A method for preparing an electronic phase change material doped with a nickel sulfide alloy compound, characterized in that Through the solid phase reaction between pre-synthesized NiS and doping element sulfide, quenching, subsequent heat treatment process and combined with the doping element composition and content design, the main steps include: (1) synthesizing a nickel sulfide parent phase by solid phase reaction with nickel and sulfur, wherein the nickel sulfide material is an α phase, has a hexagonal crystal structure, and a space group of R3mH, and does not have electronic phase transition characteristics triggered by a characteristic temperature; synthesizing a chalcogenide compound of a doping element by solid phase reaction with a doping element and sulfur, selenium, and tellurium chalcogenide elements, wherein the doping element is in a +2 valence state, has a hexagonal structure, and has a lattice parameter similar to that of β-phase nickel sulfide having electronic phase transition characteristics, and the chalcogenide compound of the doping element has semiconductor phase transport characteristics or metal-insulator phase transition characteristics with a characteristic temperature higher than room temperature; (2) The synthesized nickel sulfide parent phase and the doping element sulfide compound are ground into powder, uniformly mixed according to a certain doping ratio and cold pressed; in a vacuum or protective atmosphere, the mixed powder after cold pressing is heated to above the transition temperature from the α phase to the β phase of nickel sulfide by direct heating with a resistance wire, or optical heating, or plasma sintering triggered by a pulse current flowing through the sample, and then rapidly cooled to below room temperature after being kept warm for a period of time, thereby retaining the high-temperature β phase; thereafter, direct heating annealing or optical annealing is performed for a period of time in the temperature range of 0-100°C above the resistivity mutation temperature to eliminate the crystal defects caused by the extremely cold quenching process, so that the prepared high-temperature hexagonal structure doped nickel sulfide compound has a resistivity mutation characteristic of more than one order of magnitude in the range of the metal-insulator phase transition temperature above 0°C; (3) The doped nickel sulfide alloy compound with a high-temperature hexagonal structure prepared in step (2) has a sudden change in resistivity, infrared reflectivity, infrared transmittance, and infrared emissivity under characteristic temperature triggering, and the above characteristic temperature can be continuously adjusted in the range of 0°C to 300°C by adjusting the doping ratio of the chalcogenide compound of the doping element and nickel sulfide; The sulfide compound of the doping element in step (1) is selected from FeS, CrS, FeSe, FeTe, FeSxSe1-x; by adjusting the type of the doping element sulfide compound element and the doping ratio, the resistivity mutation temperature and resistivity mutation degree of the doped nickel sulfide alloy compound can be regulated.

2. The method for preparing the electronic phase change material doped with nickel sulfide alloy compound according to claim 1, characterized in that: The step (2) controls the heat treatment process after the nickel sulfide parent phase and the doping element sulfide compound are mixed, so as to realize the resistivity mutation characteristics of the doped nickel sulfide alloy compound near room temperature and above. The key technology is: in a vacuum or argon or helium protective atmosphere, a thick block sample is directly heated by a resistance wire to fully react with the solid phase, or a thin slice sample is optically heated to maintain the surface morphology of the film, or a plasma sintering method is triggered by a pulse current flowing through the sample; the mixed powder after cold pressing is heated to above the transition temperature of the nickel sulfide α phase to the β phase, so as to obtain β-phase nickel sulfide; after keeping the temperature for more than 12 hours, the mixture is quenched to below room temperature with liquid nitrogen or ice water mixture, so as to retain the high temperature β phase; thereafter, in a temperature range of 0-100°C above the resistivity mutation temperature, a long-term direct heating annealing for 1 to 24 hours or a short-term rapid optical annealing for 30 seconds to 5 minutes is performed to eliminate the crystal defects caused by the extremely cold quenching process, so that the prepared doped nickel sulfide compound has a metal-insulator phase transition temperature above 0 The resistivity jump characteristic exceeds one order of magnitude in the range of ℃.

3. Application of the doped nickel sulfide alloy compound electronic phase change material prepared by the method of claim 1, characterized in that: The electronic phase change material is further processed into a regular shape and made into a mutation thermistor, a strong-off logic device, a pressure sensor through electrode leads; or used for a thermochromic coating and an infrared camouflage coating.

4. The use of the doped nickel sulfide alloy compound electronic phase change material as claimed in claim 3, characterized in that: The prepared electronic phase change material is cut into small chips of regular shape, and silver or platinum electrode material is sprayed or brushed on two opposite surfaces of the chip to obtain ohmic contact, and connected to copper-nickel alloy leads by welding. Finally, it is packaged with high thermal conductivity epoxy resin sealant to prepare a sudden thermistor device and a strongly correlated logic device. The device has excellent electrical properties with a resistivity sudden change of more than one order of magnitude near room temperature and above.

5. Application of the doped nickel sulfide alloy compound electronic phase change material prepared by the method of claim 1, characterized in that: The electronic phase change material prepared in step (3) is further crushed into powder, an organic copper complex filler is added, and a coating is prepared by electrochemical deposition or vacuum deposition and applied to thermochromic and infrared camouflage coatings.